Diseño y evaluación de una prueba de PCR para detección de Brucella spp y B abortus (2014)
ABSTRACT: Problem: brucelosis is a zoonosis that affects livestock and livestock workers. This disease is characterized by the difficulties for its early diagnosis. Sensitivity of marrow and blood cultures as well as serological tests (Rose Bengal and ELISA) ranges between 15 and 70%, depending on the stage of infection. Development of rapid, sensitive, and specific diagnostic methods using molecular techniques such as PCR would allow timely diagnose and treatment of the disease. Objective: To develop and evaluate two PCR tests for detection of Brucella spp. and B. abortus.Materials and methods: primers to detect ugpA gene were designed and evaluated using Primer3 and others reported in the literature. Sensitivity and specificity were calculated for 3 groups (G) of human and bovine samples using Bayes’ theorem. G1 consisted of healthy human and healthy bovine samples (30 serum and 30 blood samples of each species); bovine blood samples were inoculated with Brucellaabortus. G2 consisted of healthy human and healthy bovine samples (30 serum and 30 blood samples of each); bovine blood samples were inoculated with Salmonella typhi, Escherichia coli, Klebsiella sp., Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus pneumonia,and Enterococcus sp. G3 consisted of 60 serum and 60 blood samples from asymptomatic bovines, as well as 60 serum and 60 blood samples from asymptomatic humans. Results: sensitivity and specificity of the PCR test to detect Brucella sp. and Brucella abortus reached 100% in human and bovine samples. Conclusiones: considering the high sensitivity and specificity observed in the PCR tests studied, we recommend doing a follow up of the test in a clinical trial to evaluate its performance in infected humans and animals.